Hydrophobicity controls guest uptake in Rh8 metallacages. (7th August 2020) - Yu, Wei-Bin; Qiu, Feng-Yi; Xin, Zhi-Feng; Sun, Po
Abstract : The hydrophobic interaction plays a key role in the host–guest systems. Abstract : The hydrophobic interaction plays a key role in the host–guest systems. We, herein, used a tetramonodentate dipyridyl ligand with a vinyl group to construct a distorted cuboid 1 with a hydrophobic inner cavity, which can encapsulate the conjugated molecules as guests by supramolecular interactions. We used NMR and UV-Vis techniques to determine the processes of the guest molecules, i.e., anthracene (ANT), pyrene, and triphenylene, which were encapsulated by the host compound and calculated their binding constants K on the basis of the results. Meanwhile, we speculated that the mechanism of the encapsulation of the guest molecules by the host was driven by the hydrophobicity in the methanol solution.